The Ankyrin Repeat Domain of the TRPA Protein Painless Is Important for Thermal Nociception but Not Mechanical Nociception. - Hwang, R.Y.; Stearns, N.A.; Tracey, W.D. (PLoS ONE, 2012)
The Drosophila TRPA channel Painless is required for the function of polymodal nociceptors which detect noxious heat and noxious mechanical stimuli. These functions of Painless are reminiscent of mammalian TRPA channels that have also been implicated in thermal and mechanical nociception. A popular hypothesis to explain the mechanosensory functions of certain TRP channels proposes that a string of ankyrin repeats at the amino termini of these channels acts as an intracellular spring that senses force. Here, we describe the identification of two previously unknown Painless protein isoforms which have fewer ankyrin repeats than the canonical Painless protein. We show that one of these Painless isoforms, that essentially lacks ankyrin repeats, is sufficient to rescue mechanical nociception phenotypes of painless mutant animals but does not rescue thermal nociception phenotypes. In contrast, canonical Painless, which contains Ankyrin repeats, is sufficient to largely rescue thermal nociception but is not capable of rescuing mechanical nociception. Thus, we propose that in the case of Painless, ankryin repeats are important for thermal nociception but not for mechanical nociception.